2020
DOI: 10.1007/s00013-020-01458-z
|View full text |Cite
|
Sign up to set email alerts
|

Möbius formulas for densities of sets of prime ideals

Abstract: We generalize results of Alladi, Dawsey, and Sweeting and Woo for Chebotarev densities to general densities of sets of primes. We show that if K is a number field and S is any set of prime ideals with natural density δ(S) within the primes, thenwhere µ(a) is the generalized Möbius function and D(K, S) is the set of integral ideals a ⊆ OK with unique prime divisor of minimal norm lying in S. Our result can be applied to give formulas for densities of various sets of prime numbers, including those lying in a Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…The result (1) was generalized by Dawsey [5] to the setting of Chebotarev densities for finite Galois extensions of Q, and further by Sweeting and Woo [22] to number fields. Later, Kural et al [17] generalized all these results to natural densities of sets of prime ideals of number field K. Let P be the set of prime ideals p ⊆ O K and we say that a subset S ⊆ P with natural density δ(S) if the following limit exists: A recent work [8] of Wang with the first and third authors of this article showed the analogue of Kural et al's result over global function fields. In the other direction, Wang [25,26,27] showed the analogues of these results over Q for some arithmetic functions other than µ.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result (1) was generalized by Dawsey [5] to the setting of Chebotarev densities for finite Galois extensions of Q, and further by Sweeting and Woo [22] to number fields. Later, Kural et al [17] generalized all these results to natural densities of sets of prime ideals of number field K. Let P be the set of prime ideals p ⊆ O K and we say that a subset S ⊆ P with natural density δ(S) if the following limit exists: A recent work [8] of Wang with the first and third authors of this article showed the analogue of Kural et al's result over global function fields. In the other direction, Wang [25,26,27] showed the analogues of these results over Q for some arithmetic functions other than µ.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…
In this article, we prove that a general version of Alladi's formula with Dirichlet convolution holds for arithmetical semigroups satisfying Axiom A or Axiom A # . As applications, we apply our main results to certain semigroups coming from algebraic number theory, arithmetical geometry and graph theory, particularly generalizing the results of [27,17,8].
…”
mentioning
confidence: 99%
“…Other authors [14,27,28] have since extended Alladi's techniques from [1], giving a variety of what we call "Alladi-like" formulas of the shape n≥2 µ * (n)f (n)/n < ∞, with µ * (n) := −µ(n) and f (n) an arithmetic function, to compute natural densities and other constants, such as this special 1 For more in-depth treatments of the partition norm, see [12,22,25]. Partitions of fixed norm n are called multiplicative partitions of n (or factorizations of n) in the literature; these were apparently first studied by MacMahon [15].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Following Oppenheim [19], the study of these objects is sometimes referred to as "factorisatio numerorum". case of a result of Kural-McDonald-Sah [14] stated as [27], equation ( 4):…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation